(untitled) (Justicia &Derecho, 2025)
The work focuses on the analysis of the proliferation of digital platforms, a consequence of the digital, innovative and disruptive environment that accompanies us. These platforms make it possible to develop and launch the provision of services or products by companies, favouring e-commerce and e-consumption. The consolidated experiences of dispute resolution on some internationally recognised platforms, the projects (some of which have failed) of the European Union and the proposals in some countries make it possible to offer different paths, depending on the type of dispute, in an asymmetrical but modulated manner, in person or digitally, and even with algorithmic solutions.